Desiderosmia: a manifestation of iron deficiency in pregnancy. Issue 3 (8th March 2022) - Harris, Katrina; Mo, Allison; Atmuri, Kiran
Abstract : A pregnant woman in her 20s presented with an excessive desire to smell a specific household cleaning product. She was found to have severe iron deficiency anaemia and her symptoms resolved following intravenous iron supplementation. She described symptoms of fatigue, shortness of breath and olfactory cravings. The specific scent could not be replicated with other smells and the woman had to significantly modify her lifestyle to accommodate the excessive desire. She had a similar experience during her prior pregnancy which resolved after the correction of severe iron deficiency anaemia. This unique symptom has been described as desiderosmia: iron deficiency manifesting as olfactory cravings. This underappreciated but useful symptom is defined as a separate entity to pica, as there is an absence of desire to ingest the product. Desiderosmia can harm mother and baby through inhalation of potentially harmful fumes; hence, women who describe this symptom should be assessed for iron deficiency anaemia.